COMPARATIVE EVALUATION OF TWO ROTARY RETREATMENT SYSTEMS FOR REMOVAL OF ROOT CANAL FILLING - Sânziana Adina Scărlătescu; Paula Perlea; Irina Maria Gheorghiu; Alexandru A. Iliescu; Alina Toma (Amaltea Medical Publishing House, 2019)
The aim of this study was to compare the efficacy of two rotary retreatment systems - ProTaper Universal Retreatment (Dentsply Sirona) and GPR Endostar (Poldent). Materials and methods. Forty lower premolar canals were shaped by ProTaper next and filled using cold lateral condensation of gutta-percha. These were divided into 2 groups (n=20) according to the retreatment systems. There were assessed the times of retreatment, the accidents that occurred and the quality of retreatment on the x-rays after the procedures. Results. Protaper system led to a medium retreatment time of 6.15 seconds per canal and 85% of the canals showed less than 20% remnants on the canal wall. GPR system led to a medium retreatment time of 7.45 seconds and 70% of the canals showed less than 20% remnants. Conclusion. Within the limitation of this study, ProTaper Universal Retreatment proved to be more rapid and efficient than GPR system.